Review Artikel : Kandungan Fitokimia dan Potensi Urang Aring (Eclipta alba L.) Sebagai Bahan Baku Obat Untuk Mengatasi Kebotakan (Hair Loss) - Angga Purnama, Dewa Julio; Dewi, Ni Luh Putu Putri (Jurnal Farmasi Udayana, 2024)
Urang-Aring (Eclipta alba L.) belongs to the genus Eclipta from the Asteraceae family. This plant has been used for generations as traditional medicine and is known to have various pharmacological activities. In this review, we discuss the in vivo testing of several extracts from the urang-aring in mice, the phytochemical compounds contained and the pharmacological activity of the urang-aring extract. The results showed that the ethanol extract, petroleum ether and ethyl acetate fraction of the methanol extract from this plant were reported to have hair growth-promoting activity. Many research studies report that there are various types of phytochemical compounds such as triterpenes, saponins, flavonoids, thiophene, kumestan, coumarins and steroids in this plant. Among these compounds, wedelolactone and ?-sitosterol are considered to be responsible for their pharmacological activity in overcoming hair loss. Wedelolactone is known to have the activity of inhibiting the expression of TGF-?1 resulting in the elongation of hair follicles. Meanwhile, ?-sitosterol works as a 5?-reductase inhibitor so that it contributes to the treatment of androgenic alopecia.